Computer-managed maintenance systems : a step-by-step guide to effective management of maintenance, labor, and inventory - Cato, William W. (Butterworth-Heinemann, 2002)
Effective resource management and reliable equipment are essential for optimum plant performance. Computer-Managed Maintenance Systems goes beyond the simple selection and implementation of a CMMS. It also defines the changes in infrastructure, management philosophy and employee skills that must be implemented to gain maximum benefits from the CMMS. The book is designed to address the information needs of all levels of plant management. In this new edition, the authors have added a chapter specifically on the latest technology, Application Solution Providers (ASP) that has revolutionized the way CMMS are used and the benefits they can offer to a business. This solution provides integrated software, hardware and networking technology along with Information Technology (IT) consulting services into an outsourced package. A new appendix on Key Performance Indicators has also been added. Comprehensive, practical guide that covers selection, justification, and implementation of an effective CMMS in any facilityAll levels of plant management will find useful information in this step-by-step guideIncludes a new chapter on ASP technologies.